2008
DOI: 10.1007/s00520-008-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of effects of a home-based physical activity program among breast cancer survivors

Abstract: Some positive effects of a home-based PA intervention for breast cancer patients were maintained at 6 and 9 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…Nevertheless, we have previously reported that participants rarely engaged in exercise types other than walking and selfreported leisure activity immediately postintervention increased, suggesting that improvements in objective activity may have been due, at least in part, to increases in leisure activity (11). With regard to the magnitude of our intervention effect months after completion, direct comparison to other studies is difficult because only two studies report longer term adherence as the change in minutes of activity (8,21). Specifically, mean change for the intervention versus control group in self-report weekly minutes has been noted to be 60 to 94 minutes (8,21).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, we have previously reported that participants rarely engaged in exercise types other than walking and selfreported leisure activity immediately postintervention increased, suggesting that improvements in objective activity may have been due, at least in part, to increases in leisure activity (11). With regard to the magnitude of our intervention effect months after completion, direct comparison to other studies is difficult because only two studies report longer term adherence as the change in minutes of activity (8,21). Specifically, mean change for the intervention versus control group in self-report weekly minutes has been noted to be 60 to 94 minutes (8,21).…”
Section: Discussionmentioning
confidence: 82%
“…It is noteworthy that our study showed a persistent, statistically significant improvement in objective physical activity. Few randomized trials in cancer survivors have shown statistically significant improvements in activity months after completing a behavior change intervention (8,9), and no prior study has shown sustained benefit based on objective monitoring. Although the primary advantage of objectively measuring physical activity is the minimization of overreporting activity levels, we acknowledge that accelerometers do not record activities such as bicycling or swimming and do not differentiate between occupational and leisure activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations